The role and mechanism of inflammatory response to growing rod implantation in early onset scoliosis - Zhang, Haoran; Han, Bingtai; Li, Zhiyi; Zhao, Yiwei; Du, You; Yang, Yang; Wang, Shengru; Zhang, Jianguo (Frontiers in Cell and Developmental Biology, 2023)
Growing rod implantation, a surgery treatment for EOS (early onset scoliosis), may cause a kind of chronic inflammation called metalosis and all other implant-related complications because of the metal debris released by the implants as a result of fraction and corrosion. There is no complete explanation of immunologic mechanisms of metalosis up to now. This review demonstrates the researches on metalosis from the clinical issues down to basic immunologic mechanisms. Adverse reactions of metal implants are mainly the formation of NLRP3 (nod-like receptor protein 3) inflammasome, primed by TLR4 (toll-like receptor protein 4), activated by phagocytosis and often accompanied by type Ⅳ hypersensitive reaction. Recent studies found that TNF-α (tumor necrosis factor α) also participates in priming, and activation of inflammasome requires disturbance of lysosome and release of cathepsin B. Ca-074Me and MCC950 are therapeutic interventions worth exploring in aseptic loosening of orthopedic implants.